Unravelling the potential of essential oils for the management of dementia: current insights - Sumit Durgapal; Prashant Kumar; Aanchal Loshali; Minky Mukhija; Bhupendra Singh; Abhishek Singh; Sushmita Uniyal; Bhuwan Chandra Joshi (Discover Applied Sciences)
Abstract Dementia, the main reason of deformity in the world, is characterised by agitation, behavioural and psychiatric symptoms, memory loss, and cognitive impairment. Managing the symptoms of individuals with dementia can be quite challenging. The current approach to treat these symptoms involves using atypical anti-psychotics off-labels, which are frequently linked to increased feeling of pain and considerably lowering the wellbeingof the patients. There are several limitations to the long-term use of these drugs; their effectiveness during the initial weeks of treatment is not maintained, and they have significant adverse effects. An important approach for managing symptoms of dementia patients would be the use of essential oils (EOs) that possess analgesic qualities and are nontoxic. Aromatic substances obtained from plants are called EOs. They can be present in bark, sap, flowers, fruits, seeds, stems, and roots. Their distinctive fragrances have both therapeutic and psychological effects. The mechanism of EOs involve activation of olfactory chemoreceptors and the initiation of various events at cellular levels in the brain regions linked to olfactory nerve. Besides, the EOs can interact with neurotransmitters like 5-HT, dopamine, GABA and transient receptor potential channels to produce the desired effects. These EOs are used in aromatherapy to improve wellness. It is one of the complementary therapies that patients, practitioners, and families find appealing because it is thought to be less likely to have negative side effects. Consequently, there is increased interest in aromatherapy backed by clinical data for the management of agitation, aggression, and psychotic symptoms. Several molecular mechanisms, either for the entire phyto-complex or for individual component, have been suggested to specify the behavioural impacts of EOs, even though a significant amount of basic research is still required. The present review discusses the clinical research studies on various EOs with their usefulness as well as limitations. Also, the goal of this review is to provide the most current, comprehensive, and detailed overview of the natural sources of EOs along with current nano-formulations based on EOs to manage and treat cognitive impairment. The limitations and challenges on the clinical use of EO shave been also discussed thoroughly along with suggestions to overcome them.